PATTERNS OF UTILIZING AI–ASSISTED TOOLS AMONG EFL STUDENTS: NEED SURVEYS FOR ASSESSMENT MODEL DEVELOPMENT - Wulyani, Anik Nunuk; Widiati, Utami; Muniroh, Siti; Rachmadhany, Clarita Dianmonica; Nurlaila, Nurlaila; Hanifiyah, Lina; Sharif, Tengku Intan Suzila Tengku (LLT Journal: A Journal on Language and Language Teaching, 2024)
This study explores patterns of AI-tool utilization among Indonesian EFL students, as preliminary data for assessment-model development. Using a convenience sampling technique, this study involved 208 university students of various year levels. A questionnaire was developed based on technology acceptance model (TAM) frameworks to collect data through Google Form, covering aspects of knowledge and use of AI tools in completing tasks, frequency of AI use and friendliness levels, reasons for using AI tools, ease of using AI tools, and desire to use AI tools. The results reveal that the participants had basic knowledge of AI but a significant number of participants admitted not knowing AI tools, suggesting the need for more education and awareness about AI. Grammarly and Google Translate were the most familiar and frequently used applications. Our findings also reveal strong relationships between perceived ease of use (PEoU) and perceived usefulness (PU) and between PU and technology acceptance (TA), implying how TAM frameworks may predict willingness to use technology-assisted or AI applications and the actual utilization. As most research participants were teacher candidates, it becomes clear that integrating AI-assisted learning content and activities appears essential as their experiences in their teacher education may influence the way they teach in the future.